FOOD IN NINETEENTH-CENTURY BRITISH HISTORY ([S.l.])
1 online resource
Keywords: For all classes, British eating habits changed dramatically in the long nineteenth century. Volume two offers a collection of sources that shed light on what people ate and cooked at home, and also while they were out and about. Cookery books are an obvious primary source, and these range from popular books aimed largely at servants responsible for providing meals to middle- and upper-class families to less lavish recipes contained in books intended for school cookery classes which would then be prepared at home.